A new species of the Scinax catharinae group (Anura, Hylidae) from Serra da Canastra, southwestern state of Minas Gerais, Brazil - Lourenço, Ana Carolina Calijorne; de Carvalho, André Luiz Gomes; Baêta, Délio; Pezzuti, Tiago Leite; Leite, Felipe Sá Fortes (Zootaxa, 2013)
We describe Scinax pombali sp. n. a new species of treefrog of the Scinax catharinae group from Serra da Canastra, mu-nicipality of Capitólio (20o36’03’’S, 46o17’34.9’’W, 987 m a.s.l.), located in the Cerrado domains of the State of Minas Gerais, Southeastern Brazil. The new species is characterized by its small size, blotches and color pattern on dorsal surface and hidden regions of flanks and thighs, canthus rostralis lightly concave and well marked, absent nuptial pad, and lack of externally differentiated inguinal gland. Additionally, we describe the tadpole of this new species, which is character-ized by the large-sized oral disc and presence of a large number of marginal papillae (two to three rows on its dorsal portion and some rows in unorganized arrangement on its lateroventral portion).